Comparison of Administering Misoprostol vs Prostaglandin E2 (PgE2) Gel in Induction of Labor at a Tertiary Care Hospital - Qasim, Tooba; Saad, Nayab; Israr, Qurat ul Ain; Babar, Sumbal; Anwar, Syeda Sumaiyya (Indus Journal of Bioscience Research, 2025)
Background: Induction of labor is a commonly employed obstetric intervention, particularly in post-dated or high-risk pregnancies. Among various pharmacological agents, misoprostol and prostaglandin E₂ (PGE₂) gel are widely used for cervical ripening and labor initiation. However, debate continues regarding their comparative efficacy, safety, and impact on maternal and neonatal outcomes. Aim: To compare the effectiveness, safety, and delivery outcomes of vaginal misoprostol versus PGE₂ gel in inducing labor among term pregnant women in a tertiary care hospital setting. Methodology: This hospital-based comparative study included 260 pregnant women admitted for induction of labor at term, randomly assigned into two groups of 130 each. Group A received 25 µg of vaginal misoprostol every 4–6 hours, while Group B received 0.5 mg of PGE₂ gel intracervically every 6 hours as per institutional protocol. Outcomes analyzed included induction-to-delivery interval, need for oxytocin augmentation, mode of delivery, maternal complications, and neonatal outcomes. Statistical analysis was performed using t-tests, chi-square tests, and Fisher’s exact tests, with p < 0.05 considered significant. Results: The misoprostol group showed a significantly shorter mean time to active labor (6.8 ± 2.3 hours vs 9.1 ± 2.7 hours; p < 0.001) and delivery (11.5 ± 3.4 hours vs 14.2 ± 4.1 hours; p < 0.001). Oxytocin augmentation was required in only 29.2% of misoprostol cases compared to 51.5% in the PGE₂ group (p = 0.001). Spontaneous vaginal delivery was significantly more frequent in nulliparous women receiving misoprostol (70.6% vs 51.4%; p = 0.018), and cesarean deliveries for failed induction were lower (3.8% vs 9.2%; p = 0.047). Maternal complications such as postpartum hemorrhage and uterine hyperstimulation were not significantly different. Neonatal outcomes, including NICU admissions and Apgar scores, were slightly better in the misoprostol group, though differences were not statistically significant. Conclusion: Vaginal misoprostol is more effective than PGE₂ gel in inducing labor, with a shorter induction-to-delivery time, reduced need for oxytocin, and higher rates of vaginal delivery, especially in nulliparous women. Its safety profile is comparable, and its lower cost and ease of use make it particularly advantageous in resource-limited tertiary settings. Misoprostol should be considered a first-line agent for labor induction where appropriate clinical infrastructure and monitoring are available.